Press Coverage of the 2023 Presidential Election Petition Tribunal: A Content Analysis of Three Selected Newspapers (The Punch, Daily Trust and Vanguard Newspapers) - Dayo, Ogunsola Surajudeen; Suleiman, Yusuf Bolakale (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2024)
The conduct of the 2023 presidential election in Nigeria has no doubt generated furor through issues that characterized the poll as captured by the media, forming the basis of a perception of many observers at home and abroad. After the poll, the wave of media frenzy that trailed the conduct of the general election shifted to the electoral tribunal. To identify how the media faired in the post-election period, particularly when attention shifted to the election tribunal, requires empirical interrogation, forming the thrust of this study. Situated within the assumptions of framing theory, the study adopted content analysis as a method; it sampled 279 copies of the three selected newspapers (The Punch, Daily Trust, and Vanguard) between August 6 and November 6, 2023. Findings showed that the Punch newspaper gave the election petition tribunal the highest prominence, with 33 stories appearing on its front page. News was the highest editorial material deployed for the coverage of the tribunal by all the selected newspapers. Three major dominant themes in the coverage were legal argument, alleged certificate forgery, and alleged attempt to compromise the justices of the tribunal. The study recommended, among others, that newspapers should continue to maintain political neutrality in Nigeria for better credibility and improved social justice.